Master of Arts In Linguistics (Kabale University, 2022)
This M.A. in Linguistics Programme is meant to be a focal theoretical linguistic base for all students pursuing Master’s studies in any of the languages offered in the Institute of Language Studies: English, French, Kiswahili and Runyakitara. This will enable the Institute to start training its own cadre of qualified members of staff. All the core theoretical courses of the Programme will be taught in general classes while the language specific components will, ifThe programme examines the principles and theories of linguistic inquiry as well as their application to the major branches of linguistics, namely: Syntax, Morphology and Phonetics (i.e. Descriptive Linguistics); Sociolinguistics; Psycholinguistics; Applied Linguistics; Comparative and Contrastive Linguistics; Semantics; Lexicography; Translation and Interpretation; Pragmatics; et cetera. Other emerging areas in the study of Linguistics, such as: Gender Linguistics and African Linguistics are also incorporated. Students are further exposed to current issues in language planning and development (including language policy development). necessary, be dealt with in the individual language subjects.